Efeito da incorporação de fosfato inorgânico e clorexidina em cimento de ionômero de vidro sobre biofilme de S. mutans - Silva, Dinah Fressato [UNESP] (2015)
The objective of this study was to determine whether the incorporation of sodium trimetaphosphate nanoparticles (TMP) and chlorhexidine increases the anti-biofilm action of glass ionomer cement (GIC) modified by resin indicated for dental restoration. The groups of this study were: 1. CIV - Fuji II LC, 2. CIV + CHX 1,25%; 3. CIV + CHX 2,5%; 4. CIV + TMP 7%, 5. CIV + CHX 1,25% + TMP7%; 6. CIV + CHX 2,5% + TMP 7%, 7. CIV + TMP 14%, 8. CIV + CHX 1,25% + TMP14%; 9. CIV + CHX 2,5% + TMP 14%. Initially, agar diffusion tests were used to test the antimicrobial effect of TMP and CHX combinations for subsequent biofilm assays. For the agar diffusion test, the microbial inoculum of Streptococcus mutans was grown in BHI broth and incubated at 37 ° C for 48 hours. Layers base of BHI agar containing 300μl of bacterial inoculum were prepared in Petri dishes. Wells with 4 mm were made in the agar and the GICs inserted them. The plates were incubated for 48 hours at 37 ° C and the inhibition zones were measured using a caliper. Data were subjected to ANOVA and Bonferroni tests(p <0.05). For the biofilm assay, six cylindrical specimens were made of metal matrices for each material group. The GIC specimens were placed in individual wells of 24-well plates and maintained in suspension within the BHI broth supplemented with 1% sucrose and 20ul of bacterial suspension. After 48 hours, biofilms were washed and stained with XTT solution (2,3-Bis- (2-Methoxy-4-nitro-5-Sulfophenyl). Then 200 uL of suspension were removed and inserted in 96-well plates for reading on a spectrophotometer. The data were submitted to the Kruskal-Wallis e Mann-Whitney test (p ≤ 0.05). The results showed that the addition of CHX significantly increases the antimicrobial activity of GIC in all tested groups and that there was a significant increase in antibiofilm action...